2020
DOI: 10.1097/md.0000000000021687
|View full text |Cite
|
Sign up to set email alerts
|

Relationships are between metformin use and survival in pancreatic cancer patients concurrent with diabetes

Abstract: Background: Increased risk and cancer-related mortality is observed in pancreatic cancer (PC) patients with diabetes mellitus (DM). Whether using metformin as glucose-lowering therapy can result in survival benefit in this group of patients is still unclear. Methods: A meta-analysis of 21 studies that including 38,772 patients was performed to investigate the association between metformin and overall survival in patients with PC and concurrent DM. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 43 publications
4
26
0
Order By: Relevance
“…When compared to normal rats, our findings from histopathology studies show that the center of islet cells is composed of ß cells (70%) with basophilic granules, while the periphery is composed of alpha cells with eosinophilic granules (25%) in the combination treatment, which aids in protecting the ß cells from further damage in DR. is study's findings are consistent with another study that found MET to play an imperative role in heart and pancreatic cells [41]. MET not only protects type 2 diabetics from CD and heart failure, but it also restores insulin secretion and protects pancreatic cells from lipotoxicity and glucotoxicity [42,43]. Furthermore, concomitant treatment of MET with GH enhances their effects and promotes pancreatic cell integrity in addition to myocardial protection.…”
Section: Discussionsupporting
confidence: 89%
“…When compared to normal rats, our findings from histopathology studies show that the center of islet cells is composed of ß cells (70%) with basophilic granules, while the periphery is composed of alpha cells with eosinophilic granules (25%) in the combination treatment, which aids in protecting the ß cells from further damage in DR. is study's findings are consistent with another study that found MET to play an imperative role in heart and pancreatic cells [41]. MET not only protects type 2 diabetics from CD and heart failure, but it also restores insulin secretion and protects pancreatic cells from lipotoxicity and glucotoxicity [42,43]. Furthermore, concomitant treatment of MET with GH enhances their effects and promotes pancreatic cell integrity in addition to myocardial protection.…”
Section: Discussionsupporting
confidence: 89%
“…For example, a meta-analysis by Dicembrini et al indicates that DPP-4i may have a potential inhibitory effect on colorectal cancer ( 98 ). A meta-analysis of 21 studies showed that metformin might be beneficial for survival in patients with pancreatic cancer and diabetes ( 99 ). Wu et al found that metformin had no effect on the overall esophageal cancer risk, but it may reduce esophageal cancer risk in T2D Asian patients ( 100 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, attention has been drawn to the fact that the frequency of various cancers is lower in subjects taking metformin. Indeed, there is a large amount of clinical evidence showing the possibility that usage of metformin decreases the risk of neoplastic transformation and enhances the response to some chemotherapies [ 94 , 95 , 96 , 97 , 98 , 99 , 100 ]. Metformin suppresses mTOR by activating AMPK in pre-neoplastic cells which leads to suppression of cell growth and an increase in apoptosis in pre-neoplastic cells ( Figure 3 ) [ 94 , 95 ].…”
Section: Metformin Suppresses Mechanistic Target Of Rapamycin (Mtomentioning
confidence: 99%